El problema religioso en la generación de 1868 : la leyenda de Dios : Valera, Alarcón, Pereda, Pérez Galdós, "Clarín", Pardo Bazán / Francisco Pérez Gutiérrez - Pérez Gutiérrez, Francisco (Persiles ; 87)
Incluye referencias bibliográficas